Optimal fiscal policy under endogenous disaster risk: How to avoid wars? - Vytautas Valaitis; Alessandro T. Villa (Federal Reserve Bank of Chicago, 2025)
We examine the role of government investment in defense capital as a deterrence tool. Using an optimal fiscal policy framework with endogenous disaster risk, we allow for an endogenous determination of geopolitical risk and defense capacity, which we discipline using the Geopolitical Risk Index. We show both analytically and quantitatively that financing defense primarily through debt, rather than taxation, is optimal. Debt issuance mitigates present tax distortions but exacerbates them in the future, especially in wartime. However, since additional defense capital deters future wars, the expected tax distortions decline as well, making debt financing a welfare-improving strategy. Quantitatively, the optimal defense financing in the presence of heightened risk involves a twice higher share of debt and backloading of tax distortions compared to other types of government spending.
Keywords: E62; D52; E60; 330; Optimal Fiscal Policy; Incomplete Markets; Endogenous Disaster Risk